Protein Tyrosine Phosphatase Nonreceptor Type 2: An Important Regulator of lnterleukin‐6 Production in Rheumatoid Arthritis Synovial Fibroblasts. Issue 10 (23rd September 2015) - Aradi, Borbala; Kato, Masaru; Filkova, Maria; Karouzakis, Emmanuel; Klein, Kerstin; Scharl, Michael; Kolling, Christoph; Michel, Beat A.; Gay, Renate E.; Buzas, Edit I.; Gay, Steffen; Jüngel, Astrid
Abstract : Objective: To investigate the role of protein tyrosine phosphatase nonreceptor type 2 (PTPN2) in the pathogenesis of rheumatoid arthritis (RA). Methods: Synovial tissue samples from patients with RA and patients with osteoarthritis (OA) were stained for PTPN2. Synovial fibroblasts were stimulated with tumor necrosis factor (TNF) and interleukin‐1β (IL‐1β), lipopolysaccharide (LPS), TRAIL, or thapsigargin. The expression of PTPN2 in synovial fibroblasts and peripheral blood mononuclear cells (PBMCs) was analyzed by real‐time polymerase chain reaction and Western blotting. Cell death, the release of IL‐6 and IL‐8, and the induction of autophagy were analyzed after PTPN2 silencing. Methylated DNA immunoprecipitation analysis was used to evaluate DNA methylation–regulated gene expression of PTPN2. Results: PTPN2 was significantly overexpressed in synovial tissue samples from RA patients compared to OA patients. Patients receiving anti‐TNF therapy showed significantly reduced staining for PTPN2 compared with patients treated with nonbiologic agents. PTPN2 expression was higher in RA synovial fibroblasts (RASFs) than in OASFs. This differential expression was not regulated by DNA methylation. PTPN2 was further up‐regulated after stimulation with TNF, TNF combined with IL‐1β, or LPS. There was no significant difference in basal PTPN2 expression in PBMCs from patients with RA, ankylosing spondylitis, or systemic lupus erythematosus or healthy controls. Most interestingly, PTPN2 silencing in RASFs significantly increased the production of the inflammatory cytokine IL‐6 but did not affect levels of IL‐8. Moreover, functional analysis showed that high PTPN2 levels contributed to the increased apoptosis resistance of RASFs and increased autophagy. Conclusion: This is the first study of PTPN2 in RASFs showing that PTPN2 regulates IL‐6 production, cell death, and autophagy. Our findings indicate that PTPN2 is linked to the pathogenesis of RA via synovial fibroblasts.